1992
DOI: 10.1038/nbt0892-888
|View full text |Cite
|
Sign up to set email alerts
|

Use of the nirB Promoter to Direct the Stable Expression of Heterologous Antigens in Salmonella Oral Vaccine Strains: Development of a Single–Dose Oral Tetanus Vaccine

Abstract: Plasmid pTETnir15, which directs the expression of the non-toxic immunogenic fragment C of tetanus toxin from the anaerobically inducible nirB promoter, was introduced into the Salmonella typhimurium aroA aroD live oral vaccine strain BRD509. The resulting strain, designated BRD847, was used to vaccinate orally BALB/c mice and was tested for plasmid stability and its ability to protect against a lethal tetanus toxin challenge. pTETnir15 was stably inherited by bacteria growing or persisting in the tissues of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
147
0
4

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(156 citation statements)
references
References 21 publications
5
147
0
4
Order By: Relevance
“…Here we have shown that foreign antigen expression driven by macrophage-inducible promotors leads to a dramatic humoral response to an antigen expressed from a single chromosomal copy. Our results utilizing Pag-alkaline phosphatase fusion antigens are comparable to previously published murine data for multicopy plasmid-encoded heterologous antigens (3)(4)(5) and superior to those for single chromosomal copies of malarial and bacterial antigens (7)(8)(9). In our experiments, even 3-to 10-fold greater constitutive expression was unable to induce humoral responses approaching those induced by phoP-regulated expression.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Here we have shown that foreign antigen expression driven by macrophage-inducible promotors leads to a dramatic humoral response to an antigen expressed from a single chromosomal copy. Our results utilizing Pag-alkaline phosphatase fusion antigens are comparable to previously published murine data for multicopy plasmid-encoded heterologous antigens (3)(4)(5) and superior to those for single chromosomal copies of malarial and bacterial antigens (7)(8)(9). In our experiments, even 3-to 10-fold greater constitutive expression was unable to induce humoral responses approaching those induced by phoP-regulated expression.…”
Section: Resultssupporting
confidence: 78%
“…Other environmentally regulated promotors postulated to be expressed in vivo, including those induced by low iron concentrations or anaerobiasis, have been utilized for expression of heterologous antigens in plasmid expression systems in Salmonella (3,35). Therefore, as another control, Shiga-like toxin I-B (SLT-IB) expressed under control of an ironregulated promotor was integrated at the pagC chromosomal locus in strain SL3261.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recombinant S. typhimurium BRD 847 strain used in the immunization study is a double aroA aroD mutant that expresses the nontoxic, immunogenic 50-kDa ToxC fragment of tetanus toxin from plasmid pTETnir15 under the control of the anaerobically inducible nirB promoter (rSalmonella-ToxC) (30). For the control, rSalmonella that are not expressing ToxC were adopted.…”
Section: Cell Stainingmentioning
confidence: 99%
“…Additionally, peptides, particularly those encoding B-cell epitopes, may be expressed by attenuated Salmonella strains as hybrid proteins following genetic fusion to bacterial proteins. This approach may improve both the stability and the immunogenicity of target antigens delivered orally in live bivalent vaccines (Dougan et al 1987, Chatfield et al 1992.…”
mentioning
confidence: 99%